Two rare species of tylenchids, Discotylenchus biannulatus n. sp. and Labrys chinensis Qing & Bert, 2018 (Nematoda: Tylenchidae) from western Iran - Konani, Ehsan; Panahandeh, Yousef; Pourjam, Ebrahim; Álvarez-Ortega, Sergio; Pedram, Majid (Zootaxa, 2018)
Two rare species of the family Tylenchidae are described and illustrated based on morphological and morphometric characters. Scanning electron microscope (SEM) studies provided details of anterior end structures, helpful in generic identification of the studied populations. Discotylenchus biannulatus n. sp. is characterized by its dorso-ventrally flattened smooth cephalic region having two proximal annuli and a rectangular perioral disc, short longitudinal amphidial slits, lateral field with four incisures, stylet 9–10 μm long, with the conus shorter than half the total stylet length and with posteriorly directed knobs, well-developed median bulb, mono-prodelphic reproductive system with rounded empty spermatheca and short postvulval uterine sac (PUS), and filiform tail with pointed end. It is compared with other species of Discotylenchus having four lines in the lateral field. The Iranian population of Labrys chinensis is characterized by its long and slender (a = 45.2–57.2) body, smooth rounded cephalic region and an offset disc-like apical labial plate, short longitudinal lateral amphidial slits, lateral field with two incisures, moderately developed stylet with the conus less than half the total length and posteriorly directed knobs, median bulb fusiform with distinct but weak valve, gradually joining the isthmus, vulva at 57.2–59.1% with small flaps, elongate conoid tail, uniformly and slightly narrowing toward end with broadly rounded terminus and rare males. The minor morphological differences of the recovered population with the type population are discussed.